หลักสูตรรายวิชาเพิ่มเติมพลศึกษาโดยใช้ทฤษฎีการตั้งเป้าหมายเพื่อเสริมสร้างสมาธิของนักเรียนประถมศึกษา - กาญจนา เรืองอำพันธุ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This research was a mixed method using quantitative and qualitative research. The objectives of this research were to; 1) study the current situations and needs of a Physical Education Additional Course Curriculum using Goal Setting Theory to enhance concentration of primary school students; 2) develop a purpose Physical Education Additional Course Curriculum. The sample groups were Physical Education Teachers, divided into an interview group of 6 experts and another QA group of 378 PE teachers, using Multi-stage sampling and ransoming using Taro Yamane from primary schools under Office of the Basic Education Commission. The instruments were a guideline question for semi-structured interviews and a survey questionnaire. The total Index of consistency (IOC) were 0.97 with reliability of 0.96. The analysis of the data was analyzed using Mean score, S.D, and PNI modified index. The research findings were as follows; Research result found that the course curriculum composed of 4 composition; 1) Objectives should focus on the concentration, moral, physical fitness, knowledge, skills and attitude; 2) Contents should include adapted Thai sports games with concentration focused, meaningful learning from games group, beside the core content of national curriculum; 3) learning activities should focus on basic movement, rhythmic movements; 4) Assessment should be well planning using tests specification, validated analyze the quality of the tests and back up the evaluation data.